2013
DOI: 10.1074/jbc.m113.508606
|View full text |Cite
|
Sign up to set email alerts
|

A Crystal Structure of the Dengue Virus Non-structural Protein 5 (NS5) Polymerase Delineates Interdomain Amino Acid Residues That Enhance Its Thermostability and de Novo Initiation Activities

Abstract: Background: The NS5 protein from dengue virus comprises a methyltransferase and a polymerase domain connected by a linker region. Results: Linker residues enhance polymerase activity and thermostability. Conclusion: A crystal structure of the dengue virus polymerase reveals that linker residues contribute to protein stability. Significance: These results should accelerate the development of antivirals against dengue virus, a major human pathogen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
87
3
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 82 publications
(98 citation statements)
references
References 27 publications
(40 reference statements)
6
87
3
2
Order By: Relevance
“…The extended DENV-3 and DENV-4 RdRp domains, which contain additional residues at the N terminus of the protein, were expressed with an N-terminal AVI-tag for site-specific biotinylation during expression in E. coli. The additional residues at the N terminus of the RdRp domain improve the stability and enzymatic activity of the domain (15). The additional residues also improved the stability of the protein on the chip surface and reduced nonspecific binding (data not shown).…”
Section: Jf-31-mg46 Binds To Denv-3 and Denv-4 Rdrp By Spr-mentioning
confidence: 86%
See 1 more Smart Citation
“…The extended DENV-3 and DENV-4 RdRp domains, which contain additional residues at the N terminus of the protein, were expressed with an N-terminal AVI-tag for site-specific biotinylation during expression in E. coli. The additional residues at the N terminus of the RdRp domain improve the stability and enzymatic activity of the domain (15). The additional residues also improved the stability of the protein on the chip surface and reduced nonspecific binding (data not shown).…”
Section: Jf-31-mg46 Binds To Denv-3 and Denv-4 Rdrp By Spr-mentioning
confidence: 86%
“…DENV-4 NS5 was expressed and purified as described previously (10). DENV-3 and -4 RdRp constructs for surface plasmon resonance (SPR) analyses comprised N-terminal AviTag sequences (14) linked to residues 263-900 (DENV-3) or residues 264 -900 (DENV-4) via PCR (primers are listed in supplemental Table S1) and cloned into the vector pET28a bearing a PreScission protease cleavage site (15) inserted downstream of the vector N-terminal His tag sequence. Expression plasmids for AviTag DENV3 or DENV4 RdRp proteins were co-transformed into BL21 cells with an expression plasmid for biotin protein ligase, BirA of E. coli, and proteins were purified as described previously (13).…”
Section: Methodsmentioning
confidence: 99%
“…This de novo initiation assay (dnI) enabled us to perform a screening campaign with a more thermo-stable DENV4 RdRp domain and to develop a flow-chart for hit followup activities (Smith et al, 2014;Lim et al, 2013). In this report, we describe the detailed characterization of dengue polymerase dnI activity and the conditions that stabilized the protein.…”
Section: Introductionmentioning
confidence: 95%
“…Small-angle X-ray scattering (SAXS) studies suggested that NS5 could adopt different conformations permitted by a flexible linker (13). Interestingly, an Nterminally extended RdRp spanning residues from 265 to 900 improved thermostability and RdRp activity compared with a shorter RdRp spanning residues 273 to 900 (14). More recently, the structures of the full-length NS5 protein from DENV3 (15) and Japanese encephalitis virus (JEV) full-length NS5 (PDB code 4K6M) (16) have been resolved.…”
Section: N Onstructural Protein 5 (Ns5) Is a Multifunctional Protein mentioning
confidence: 99%